Impact of diabetes mellitus on osteoarthritis: a scoping review on biomarkers - Seow, Shi Rui; Mat, Sumaiyah; Ahmad Azam, Amalina; Rajab, Nor Fadilah; Safinar Ismail, Intan; Singh, Devinder Kaur Ajit; Shahar, Suzana; Tan, Maw Pin; Berenbaum, Francis (Cambridge University Press, 2024)
Osteoarthritis (OA) commonly affects the knee and hip joints and accounts for 19.3% of disability-adjusted life years and years lived with disability worldwide (Refs 1, 2). Early management is important in order to avoid disability uphold quality of life (Ref. 3). However, a lack of awareness of subclinical and early symptomatic stages of OA often hampers early management (Ref. 4). Moreover, late diagnosis of OA among those with severe disease, at a stage when OA management becomes more complicated is common (Refs 5, 6, 7, 8). Established risk factors for the development and progression of OA include increasing age, female, history of trauma and obesity (Ref. 9). Recent studies have also drawn a link between OA and metabolic syndrome, which is characterized by insulin resistance, dyslipidaemia and hypertension (Refs 10, 11).